Extraction of valuable compounds from winter melon (Benincasa hispida (thunb.) cogn.) seeds using ultrasonic-assisted solvent, supercritical carbon dioxide and pressure-swing methods - Bimakr, Mandana (2012)
Different extraction techniques have been used to isolate valuable compounds from different plants. Conventional Soxhlet extraction (CSE) is a standard technique which has been used for a long time. The main disadvantages of conventional techniques are long extraction time which is not always accepted by industries. This extraction method is also not suitable for the extraction of thermo-sensitive compounds due to the possibility of thermal decomposition of target compounds as extraction usually occurs at the boiling point of used solvent for a long time. The current study presented the effect of various extraction methods including conventional Soxhlet extraction (CSE), ultrasound-assisted extraction (UAE),supercritical carbon dioxide (CO2) extraction (SCE) and SCE with pressure swing technique (SCE-PST) for extraction of valuable compounds from winter melon (Benincasa hispida (Thunb.) Cogn.) seeds. Parameters examined were crude extraction yield (CEY), radical scavenging activity (RSA) in terms of 1, 1-diphenyl 2-picrylhydrazyl (DPPH˙) radicals scavenging percentage (%DPPHsc) and 2,2´-Azinobis (3-ethylbenzothiazoline-6-sulphonic acid) diammonium salt (ABTS+˙) radicals scavenging percentage (%ABTSsc) and total phenolic content (TPC) of B.hispida seeds. The overall optimum conditions for obtaining maximum dependent variables were predicted using response surface methodology (RSM). Under the optimised conditions, the fatty acid composition of extracts was identified and quantified using gas chromatography (GC). In CSE different solvents (n-hexane, ethanol and ethyl acetate) were used and the highest CEY (294.45 ± 1.22 mgg-1) obtained using ethyl acetate. Ethanol (EtOH) extracts showed the highest %DPPHsc and %ABTSsc (28.7 ± 0.7 and 27.0 ± 0.9, respectively) while n-hexane extracts possessed the lowest (13.1 ± 0.9 and 12.2 ± 0.6, respectively). TPC ranging from zero in n-hexane extract to 11.34 ± 1.3 mg GAE/g extracts obtained using EtOH which revealed the antioxidant potency of B. hispida seeds. In order to improve the quality and quantity of the extracts, UAE was applied and significant (p<0.05) effect of amplitude, temperature and sonication time was detected. The overall optimum conditions predicted to be 65% amplitude, 52 ºC and 35.00 min. under the optimum conditions the CEY, %DPPHsc, %ABTSsc and TPC were 108.50 mgg-1, 43.47%, 36.47% and 23.97 mg GAE/g extract. In the following,the SCE was investigated and it was found that studied parameters (pressure, temperature and dynamic extraction time) significantly (p<0.05) affected the dependent variables. The optimum conditions found to be 234.25 bar, 46 ºC and 95.05 min and under this optimum condition, the CEY, %DPPHsc, %ABTSsc and TPC were 174.91 mgg-1, 52.96%, 61.65% and 40.45 mg GAE/g extract,respectively. Finally, SCE-PST was investigated at different levels of pressure,holding time and continuous extraction time. The significant (p<0.05) difference in responses revealed the crucial and effective role of PST for improving the SCE process. The overall optimum conditions predicted to be 179.18 bar, 10.15 min holding time and 52.47 min continuous extraction time. Under the optimum condition the CEY, %DPPHsc, %ABTSsc and TPC were 235.12 mgg-1, 67.36%,64.42% and 42.77 mg GAE/g extract, respectively. Significant difference (p<0.05) for fatty acid composition was found between CSE and various extraction methods while considerable difference is not found between the unsaturated fatty acids (UFAs) content of extracts using UAE (82.00%), SCE (83.67%) and SCE-PST (84.34%). Generally, the dominant composition of the UFAs was linoleic acid (C18:02) and oleic acid (C18:01). This study, for the first time, confirmed the possibility of using UAE, SCE and SCE-PST to obtain the valuable extracts with high antioxidant potency and containing high amount of UFAs from B. hispida seeds.